Transformation of Village Entrepreneurship: Financial Literacy as a Driver of Economic Independence for Borrowers of BUMDesa Bersama in Serang Regency: Transformasi Kewirausahaan Desa: Literasi Keuangan sebagai Pendorong Kemandirian Ekonomi Bagi Debitur BUMDesa Bersama di Kabupaten Serang - Taufik Raharjo; Maman Suhendra; Ambang Aries Yudanto; Tanda Setiya; Erny Arianty (Institut Riset dan Publikasi Indonesia, 2025)
The aim of this community service (PKM) initiative is to facilitate the improvement of financial literacy among debtors of BUMDesma LKD across Serang Regency. The execution of this PKM activity was conducted in three phases: Planning, Implementation, and Evaluation to attain best outcomes. During the planning phase, the team formulated the PKM activity idea, which consists of three primary steps: assessing the financial management attributes of the borrowers, delivering financial management training to the debtors, and offering post-training mentorship. In the implementation phase, debtor characteristics were discerned through observations and interviews of 22 debtors from 18 BUMDesma LKD throughout 17 sub-districts in Serang Regency. The second stage entailed administering financial management instruction for the debtors utilizing a practical financial management methodology known as